Kevalidan LKPD Berorientasi Model Problem Based Learning Materi Gaya Kelas IV SDN 24 Pontianak Tenggara - Karwadi, Tamara; Kartono, Kartono; Pranata, Rio (AS-SABIQUN, 2024)
This research and development aims to produce a Problem-Based Learning (PBL) model-oriented Student Worksheet (LKPD) product for the Science and Social Studies (IPAS) subject, specifically focusing on the topic of the influence of forces on objects for fourth-grade elementary school students. The objective is to create a valid and suitable tool to assist the learning process within the Independent Learning Curriculum. The method employed is the research and development (R&D) approach, adapting the ADDIE model and modifying it into ADD. The research sample consists of 2 validators and 24 students. Data collection techniques include questionnaires and interviews. The results of the research and development received feasibility assessments from 2 validators, with an average score of 4 for the didactic aspect, categorized as "Highly Feasible". The aspect of suitability regarding the orientation of the problem-based learning model obtained an average score of 3.95, also categorized as "Highly Feasible". The construction aspect received an average score of 3.83, likewise categorized as "Highly Feasible". Additionally, the design aspect obtained an average score of 3.85, also categorized as "Highly Feasible", for the developed PBL-oriented LKPD. These results are supported by the readability test and student response towards the LKPD, which yielded excellent results. The readability test obtained a percentage score of 84.98%, categorized as "Very Good". In conclusion, it can be inferred that the PBL-oriented LKPD is suitable for use in the learning process.